Sexual dysfunction in the climacteric period and associated factors - Jaqueline Teixeira Teles Gonçalves; Camila Teles Gonçalves; Kássia Héllen Vieira; Renata Ferreira Santana; Vivianne Margareth Chaves Pereira Reis; Marise Fagundes Silveira (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to evaluate associated factors with sexual dysfunction among middle-aged women. Methods: cross-sectional and analytical study was carried out with climacteric women attended at a Family Health Strategy Unit in the city of Montes Claros, MG. Brazil. The eligible women answered a question form containing sociodemographic, behavioral, anthropometric, gynecological factors and sexuality. The Body Mass Index and waist circumference were used to assess nutritional status and metabolic risk. To evaluate quality of life and sexual performance the Menopause Rating Scale and the Sexual Quotient - Female Version were used, respectively. Bivariate analysis and hierarchical multiple regression were used to identify associated factors with sexual dysfunction in the climacteric period. Results: among 195 women, 29.6% had sexual dysfunction. The prevalence of unsatisfactory sexual performance was higher among women who reported moderate to severe climacteric symptoms (OR=2.47) and lower schooling level was also associated (OR=1.95). However, age at menarche below 12 years (OR=0.43) and non-white (OR=0.36) seem to have a protective effect for good sexual performance. Conclusion: the prevalence of sexual dysfunction was high and the level of schooling and climacteric symptomatology were associated factors with this outcome.